Nursing students’ perceptions on Objective Structured Clinical Examination (OSCE) - Aung, Khin Thandar; Zakaria, Anis Nur Al Basirah (Chandramma Education Society, 2016)
Background: Objective Structured Clinical Examination (OSCE) has been widely used in the assessment of students’ clinical performance. One of the strategies to improve the effectiveness is through assessing feedback from students on OSCE. These data are important to ensure the learning objectives of the OSCE are achieved besides to improve the effectiveness and to ensure it will be practicable in clinical settings. Objective: This study aims to identify nursing students’ perceptions on OSCE. Methodology: A cross sectional study using convenience sampling was conducted among 91 nursing students who have experienced in sitting OSCE in International Islamic University Malaysia (IIUM), Kuantan, Pahang, Malaysia. Results: The findings showed that the majority of respondents (85.3 percent) has the positive perception on OSCE whilst 14.7 percent of respondents have the negative perception. For the association between socio-demographic and year of study and gender, it showed both have no significant association with the nursing students’ perception. Conclusion: The majority of respondents was identified to have positive perceptions on OSCE. However, some of them have negative perceptions on OSCE. Thus, the relevant authorities should take a step to improve the quality of OSCE exam, as well as its accuracy and reliability. It is hoped that the OSCE will be one of the main assessment in IIUM and other health care courses at the other universities.